Espinela Li2CoTi3O8 nanométrica obtenida para aplicación como pigmento - Da Câmara, Maria Suely Costa; Pimentel, Lidiane Alves; Longo, Elson [UNESP]; Da Nobrega Azevedo, Luciano; De Araújo Melo, Dulce Maria (Elsevier, 2016)
Pigments are used in ceramics, cosmetics, inks, and other applications widely materials. To this must be single and easily reproducible. Moreover, the pigments obtained in the nanoscale are more stable, reproducible and highlight color in small amounts compared with those obtained in micrometer scale. The mixed oxides with spinel structures AB2O4 have important applications, including: pigments, refractories, catalytic and electronic ceramics. In this context, the aim of this work was the preparation of powder Li2CoTi3O8 spinel phase with nanometer particle size of the polymeric precursor method (Pechini) and characterization by means of thermal analysis (TG/DTA) X-ray diffraction (XRD), refined by the Rietveld method, BET, transmission electron microscopy (TEM), Raman and colorimetric coordinates. The pigment was obtained by heat treatment of 400 °C to 1000 °C after pyrolysis at 300 °C/1 h for removing the organic material. Li2CoTi3O8 desired spinel phase was obtained from 500 °C, and presenting stability nanometer to about 1.300 °C. Spinel green phase introduced at temperatures in the range of 400 °C and 500 °C, and 600 °C at temperatures between blue and 1000 °C.
Spinel Li2CoTi3O8 nanometer obtained for application as pigment
Keywords: Li2CoTi3O8; Spinel